La personalidad y la conducta adaptativa en los estudiantes de la Unidad Educativa “Pedro Vicente Maldonado" - Córdova Córdova, Karen Mishell (2022)
The presently investigation has an object of research, determine the relationship between Personality and Adaptive Behavior of ninth grade students of Basic General Education of the Pedro Vicente Maldonado High School. Understanding that Personality is known as that set of characteristics, thoughts, feelings, emotions that differentiate us from each other, which intervenes at the time of developing an adequate adaptive behavior to respond of the demands on the environment. Within the methodology used in the present study, a quantitative approach was used, since a data collection was carried out, with a non-experimental design by not manipulating the variables, basic type and bibliography when using books and electronic journals for their analysis. This Scientific research, by the descriptive level, the characteristics of the variables and correlation were known when identifying the link between personality and adaptive behavior, the population was made up of the students of Pedro Vicente Maldonado High School, with an intentional sampling of 40 students , the technique was the psychometric test and the instruments were the BF-5 Test and the ABS-S-2 Test, by means of which the data collection was carried out, which were interpreted by means of tables and statistical tables, also we used SPSS statistical program, which allowed corroborating the existing correlation. Reaching the conclusion that when it existed a variety in the types of personality that can be developed and formed in an individual, the adaptive behavior of students will be different depending on the cases or situations, affecting effective adaptation to the present environment, however, is unprofessional generalize these specifications but, these would help us to avoid difficulties in future process teaching - learning.